Kefir enhances stress resilience and mitigates PTSD-related behavioral and hematological changes in mice - Balatskyi, Vitalii A.; Dmytriv, Tetiana R.; Divnych, Andrii; Lushchak, Volodymyr I. (Frontiers in Physiology, 2025)
Post-traumatic stress disorder (PTSD) is a complex psychiatric condition characterized by behavioral, cognitive, immunological, and neurochemical disturbances following traumatic experiences. Despite various therapeutic approaches, effective long-term treatments remain limited, highlighting the need for preventive strategies that enhance stress resilience. In this study, we evaluated the impact of long-term kefir consumption on behavioral, hematological, and biochemical parameters in a mouse model displaying some PTSD-like features, particularly fear- and anxiety-related behaviors induced by acute inescapable stress. Male C57BL/6J mice received kefir daily for 2 months before stress induction via electric foot shocks and continued supplementation for five additional months during recovery. Behavioral testing demonstrated that kefir-fed mice exhibited reduced anxiety-like behaviors, including increased exploration in the open field, elevated plus maze, and light/dark box tests. These mice also showed fewer freezing episodes in the aversive context test, indicating attenuated fear memory. Hematological analysis revealed a modest reduction in erythrocyte count and monocytes, alongside elevated paraoxonase (PON) activity, suggesting enhanced antioxidant defense and a shift toward anti-inflammatory immune responses. RT-qPCR analysis of the cerebral cortex showed increased steady-state transcript levels of genes involved in oxidative stress response and neuroprotection (TXNRD1, UGDH, HSPB8, GADD45B, PPARGC1A) and decreased levels of the pro-inflammatory cytokine gene IL6 transcript. These results indicate that long-term kefir intake mitigates stress-induced behavioral and physiological alterations, likely through modulation of immune and oxidative stress pathways. Taken together, our findings support the potential of kefir as a functional dietary intervention for promoting stress resilience and alleviating PTSD-like symptoms, possibly via mechanisms involving the gut-brain axis.